Delaunay mesh generation - Cheng, Siu-Wing.; Dey, Tamal K. (Tamal Krishna), 1964-; Shewchuk, Jonathan (Boca Raton, Fla. : Taylor & Francis, 2013)
"Going beyond, yet thoroughly rooted to theory, this book provides a comprehensive look at the algorithms that can produce quality Delaunay meshes through a paradigm called the Delaunay refinement. The authors describe meshing algorithms that can be built on the Delaunay refinement paradigm along with the involved mathematical analysis. In addition to introducing the theoretical foundation of meshing, the text discusses practical issues associated with the use of these algorithms and explores new developments in guaranteed meshing. The book also includes pseudo code as well as downloadable computer programs for meshing"--
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nets (Mathematics); Numerical grid generation (Numerical analysis); Triangulation; Electronic books